2018
DOI: 10.1039/c7se00513j
|View full text |Cite
|
Sign up to set email alerts
|

Dual functions of zirconium modification on improving the electrochemical performance of Ni-rich LiNi0.8Co0.1Mn0.1O2

Abstract: The main shortcomings of NCM811 could be solved at the same time via a facile Zr surface modification approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
67
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 143 publications
(69 citation statements)
references
References 47 publications
1
67
1
Order By: Relevance
“…In addition, with the development of modern society, lithium-ion batteries have gradually moved toward high specific energy. Researchers [2][3][4][5][6][7][8]. The energy density can be improved by increasing the charging voltage, which will lead to serious side reactions and safety issues.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, with the development of modern society, lithium-ion batteries have gradually moved toward high specific energy. Researchers [2][3][4][5][6][7][8]. The energy density can be improved by increasing the charging voltage, which will lead to serious side reactions and safety issues.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that in most cases, surface coating,, and removal of Li residual compounds, not only improve the cycling stability but also enhance the rate capability of layered cathode materials. Without exceptions, however, all these treatments require additional precipitating (or washing) and heating processes, leading to an increase in the cost of battery manufacture.…”
Section: Introductionmentioning
confidence: 99%
“…The calculated Li‐ion diffusion coefficient of the two electrodes are shown in Table 1 , with the calculation details being shown in Figure S13, Supporting Information. [ 40 ] Interestingly, both CC/1T‐MoS 2 and CC electrodes have stable Li ion diffusion coefficients that are on‐par. For CC/1T‐MoS 2 , they are 4.8 × 10 −10 , 3.6 × 10 −10 , and 3.2 × 10 −10 cm 2 s −1 after cycle 10, 50, and 500.…”
Section: Resultsmentioning
confidence: 99%